Virtual Relationship with Updates (Journal of Human Sciences, 2021)
Praise be to God, and may blessings and peace be upon the Messenger of God and his family, companions and those who followed him: the topic of the research is summarized in the explanation of the relationship between two schools of Islamic jurisprudence.  They took great care of the hadith of the Messenger of God, may God bless him and grant him peace, and the effects of the predecessors.  They are the school of the people of hadith (the hadiths) and the school of the people of al-Zahir (al-Dhahirah), and in order to clarify the relationship between them, it is necessary to explain the principles on which they depend in extracting rulings, and their method of deriving rulings from these principles that they adopted, and the importance of the topic also lies in highlighting the features of these two schools, and stating their origin  , And their most prominent characteristics, and the most important pros and cons